2018
DOI: 10.1002/2017gb005781
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term and Seasonal Trends in Estuarine and Coastal Carbonate Systems

Abstract: Coastal pH and total alkalinity are regulated by a diverse range of local processes superimposed on global trends of warming and ocean acidification, yet few studies have investigated the relative importance of different processes for coastal acidification. We describe long‐term (1972–2016) and seasonal trends in the carbonate system of three Danish coastal systems demonstrating that hydrological modification, changes in nutrient inputs from land, and presence/absence of calcifiers can drastically alter carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Because of the important role of conservative mixing between marine and freshwater endmembers in controlling the alkalinity distribution (Brust & Newcombe, ; Carpenter et al, ; Cifuentes et al, ; Mook & Koene, ; Park et al, ; Pelletier & Lebel, ; Turekian, ; Wong, ), long‐term trends in watershed alkalinity (Carstensen et al, ; Drake et al, ; Kaushal et al, ; Raymond et al, ; Raymond & Oh, ; Stets et al, ) must be having some influence on estuarine alkalinity. Additionally, nonconservative behavior due to biogeochemical transformations involving sulfur (Cai et al, ; Raymond et al, ; Smith & Hollibaugh, ; Yao & Millero, ), calcium (Hu et al, ; Liu et al, ; Manickam et al, ; Wartel & Faas, ), and nitrogen (Abril & Frankignoulle, ; Dai et al, ; Frankignoulle et al, ), or a combination of these factors (Abril et al, ; Cai et al, ; Cai & Wang, ; Carstensen et al, ; Cerco et al, ) has been identified. However, fewer studies have quantified rates of alkalinity consumption or production within estuaries (Brodeur et al, ; Cai & Wang, ; Cerco et al, ; Joesoef et al, ; Raymond et al, ; Smith & Hollibaugh, ; Wang & Cai, ) and we are unaware of any studies that have examined seasonal and decadal variability of alkalinity across multiple tidal tributaries of the same estuary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the important role of conservative mixing between marine and freshwater endmembers in controlling the alkalinity distribution (Brust & Newcombe, ; Carpenter et al, ; Cifuentes et al, ; Mook & Koene, ; Park et al, ; Pelletier & Lebel, ; Turekian, ; Wong, ), long‐term trends in watershed alkalinity (Carstensen et al, ; Drake et al, ; Kaushal et al, ; Raymond et al, ; Raymond & Oh, ; Stets et al, ) must be having some influence on estuarine alkalinity. Additionally, nonconservative behavior due to biogeochemical transformations involving sulfur (Cai et al, ; Raymond et al, ; Smith & Hollibaugh, ; Yao & Millero, ), calcium (Hu et al, ; Liu et al, ; Manickam et al, ; Wartel & Faas, ), and nitrogen (Abril & Frankignoulle, ; Dai et al, ; Frankignoulle et al, ), or a combination of these factors (Abril et al, ; Cai et al, ; Cai & Wang, ; Carstensen et al, ; Cerco et al, ) has been identified. However, fewer studies have quantified rates of alkalinity consumption or production within estuaries (Brodeur et al, ; Cai & Wang, ; Cerco et al, ; Joesoef et al, ; Raymond et al, ; Smith & Hollibaugh, ; Wang & Cai, ) and we are unaware of any studies that have examined seasonal and decadal variability of alkalinity across multiple tidal tributaries of the same estuary.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that alkalinity is changing in estuaries (Carstensen et al, 2018;Gustafsson et al, 2019;Hu et al, 2015;Müller et al, 2016;Prasad et al, 2013). Because of the important role of conservative mixing between marine and freshwater endmembers in controlling the alkalinity distribution (Brust & Newcombe, 1940;Carpenter et al, 1975;Cifuentes et al, 1990;Mook & Koene, 1975;Park et al, 1971;Pelletier & Lebel, 1979;Turekian, 1971;Wong, 1979), long-term trends in watershed alkalinity (Carstensen et al, 2018;Drake et al, 2018;Kaushal et al, 2013;Raymond et al, 2008;Raymond & Oh, 2009;Stets et al, 2014) must be having some influence on estuarine alkalinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A net internal total alkalinity (TA) generation has the potential to increase the capacity of the coastal ocean buffer and the uptake of atmospheric carbon dioxide (CO 2 ) (Brasse et al ; Chen ; Wallmann et al ; Thomas et al ; Hu and Cai ; Krumins et al ; Carstensen et al ). However, estimates of global TA generation from anaerobic processes in continental shelves and oxygen minimum zones are widely variable (Gustafsson et al ), ranging from 4–5 Tmol yr −1 (Hu and Cai ) to 16–31 Tmol yr −1 (Chen ; Thomas et al ).…”
mentioning
confidence: 99%
“…In the most recent global synthesis of estuarine CO 2 outgassing (Chen et al, 2013), data from 165 estuaries were included, but only 29 systems had seasonal coverage and only 16 of these had published studies of their p CO 2 dynamics (Àlvarez et al, 1999; Frankignoulle et al, 1998; Guo et al, 2009; Jiang et al, 2008; Koné et al, 2009; Mukhopadhyay et al, 2002; Raymond et al, 2000; Zhai et al, 2007). Fewer still had interannual coverage, with 13 of the 16 published seasonal studies covering a time period of less than 2 yr and the remaining 3 consisting of up to nine cruises over as many as 5 yr. Of the studies published since the synthesis of Chen et al (2013), we are only aware of three that cover more than a few years (Carstensen et al, 2018; Dinauer & Mucci, 2017; Prasad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%